Phases & stages : the Terri Clark journals. - Clark, Terri (Insomniac Press, 2003)
What's it like being a singer, songwriter, guitarist, and superstar? For multi-platinum selling country songstress Terri Clark, it's a world of tour buses, friendly faces, and passing moments captured in songs. Having kept a journal during her rise from breakout sensation to first woman in almost a year to have a number one country hit with her ''I Just Wanna Be Mad, '' Phases & Stages affords an unprecedented insight into the price of the dream, the joy of creation, and the thrill of arrival. With a candor often unseen in today's airbrushed-for-your-protection world, Clark exhibits the strengt.